Learning from seasoned evaluators: Implications of systems approaches for evaluation practice. (April 2017) - Gates, Emily F.
In the last 20 years, approaches (i.e. concepts, theories, methods) from the systems fields have increased in popularity among evaluators and evaluation commissioners. Their popularity stems in part from a widespread view that systems approaches transform evaluation practice, despite a lack of evidence. There have been few empirical examinations of the implications of these approaches for evaluation practice. This study analyzed eight cases of seasoned evaluators using systems approaches in diverse areas of evaluation practice to identify implications for how these professionals practice evaluation. Case materials included semi-structured interviews with each evaluator and descriptions of evaluations they conducted. Findings support a variety of case-specific transformations rather than a wholesale transformation in evaluation practice. Future directions for evaluator training, evaluation commissioning and contracting, and research are identified.